The Role of Oxidative Stress and Autophagy in Atherosclerosis - Perrotta, Ida (Oxid Med Cell Longev, 2015)
Atherosclerosis is a multifactorial, multistep disorder of large- and medium-sized arteries involving, in addition to age, gender and menopausal status, a complex interplay between lifestyle and genetic risk factors. Atherosclerosis usually begins with the diffusion and retention of atherogenic lipoproteins into the subendothelial space of the artery wall where they become oxidized by local enzymes and accumulate, leading to the formation of a cushion called atheroma or atheromatous or fibrofatty plaque, composed of a mixture of macrophages, lymphocytes, smooth muscle cells (SMCs), cholesterol cleft, necrotic debris, and lipid-laden foam cells. The pathogenesis of atherosclerosis still remains incompletely understood but emerging evidence suggests that it may involve multiple cellular events, including endothelial cell (EC) dysfunction, inflammation, proliferation of vascular SMCs, matrix (ECM) alteration, and neovascularization. Actually, a growing body of evidence indicates that autophagy along with the chronic and acute overproduction of reactive oxygen species (ROS) is integral to the development and progression of the disease and may represent fruitful avenues for biological investigation and for the identification of new therapeutic targets. In this review, we give an overview of ROS and autophagy in atherosclerosis as background to understand their potential role in this vascular disease.